2016
DOI: 10.1038/srep34138
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq analysis of the hypothalamic transcriptome reveals the networks regulating physiopathological progress in the diabetic GK rat

Abstract: The Goto-Kakizaki (GK) rat is an animal model of non-obese type 2 diabetes (T2D). The GK rat was generated through the introduction of various genetic mutations from continuous inbreeding; these rats develop diabetes spontaneously. The mutated genes in GK rats may play key roles in the regulation of diabetes. The hypothalamus plays a central role in systematic energy homeostasis. Here, the hypothalamic transcriptomes in GK and Wistar rats at 4, 8 and 12 weeks were investigated by RNA-seq, and multiple variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Lee [33] found this enzyme in the ovary of rats. Animal studies have shown that ADCY3 plays an important role in the regulation of the hypothalamus of rats [34]. In addition, ADCY3 is highly expressed in olfactory epithelial cells [35] and is primarily responsible for the detection of odors.…”
Section: Discussionmentioning
confidence: 99%
“…Lee [33] found this enzyme in the ovary of rats. Animal studies have shown that ADCY3 plays an important role in the regulation of the hypothalamus of rats [34]. In addition, ADCY3 is highly expressed in olfactory epithelial cells [35] and is primarily responsible for the detection of odors.…”
Section: Discussionmentioning
confidence: 99%
“…DEGs analysis revealed that 726 genes were significantly altered in GK rats compared with Wistar rats. Of these DEGs, 507 genes were also identified in our previous study of the hypothalamic transcriptome in GK rats (Meng et al, 2016). The partial differences of GK rat transcriptomic profiles in two studies might be related to the change in the breeding environment (Portha et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Research has shown that hypothalamic dysfunctions contribute to the development of chronic conditions, such as T2D (Jais & Bruning, 2017; Chowen et al, 2016). We previously detected the disorder of transcriptome in the hypothalamus through RNA sequencing (RNA-Seq) analysis, which might be associated with pathogenesis in diabetic GK rats (Meng et al, 2016). Physical activity is a critical element in the management and prevention of T2D by improving blood glucose and insulin action (De Feo & Schwarz, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The genome sequencing of 10 GK rats and 10 Wistar rats (8 weeks old) were purchased from SLAC Laboratory Animal Co., Ltd. (Shanghai, China). All rats used in this study were same with our previous study (Meng et al, 2016), which were approved by the institutional review board of the Guangdong Key Laboratory of Laboratory Animals. All protocols were carried out in accordance with the approved guidelines of the Institutional Animal Care and Use Committee, Ethic Certificate No: IACUC2014029.…”
Section: Methodsmentioning
confidence: 99%